Użycie narracji wizualnej w micie i Filomeli i Prokne - Zadka, Małgorzata (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
The aim of this article is to present a part of the myth of Philomela and Procne, associated with the sending of a message embroidered on fabric. This apparel not only must be treated as an alternative form of communication, but also as a visual narrative, characteristic rather of graphical representations. Showing this type of object in a literary context was not accidental, but resulted from a good understanding of their cultural role.
Keywords: Greek mythology; iconography; Philomela; Procne; Tereus